2009
DOI: 10.1007/s11249-009-9521-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Friction Noise Versus Contact Area of Rough Surfaces Weakly Loaded

Abstract: This study presents an experiment to measure the dependence of friction noise versus the nominal contact area. The friction-induced vibration is generated by the sliding of two rough surfaces. The normal load is low leading to a weak contact. The normal load and the sliding velocity are maintained constant. The nominal contact area ranges over two orders of magnitude. It is found that two regimes exist. On the one hand, the vibration energy is proportional to the contact area. But on the second hand, the vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The static equilibrium is easily obtained as u s = (N/K) 2/3 . Introducing the new variable q defined by u = u s (1 + 2 3 q), u = 2us 3 q and ü = 2us 3 q leads to: 2mu s 3 q + Ku s 3/2 (1 + 2αu s 3 q)(1 + 2 3 q) 3/2 = N. (19) Now we can linearise the motion equation around the static equilibrium q = 0, that is:…”
Section: Appendix: Multi-asperity Contact Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The static equilibrium is easily obtained as u s = (N/K) 2/3 . Introducing the new variable q defined by u = u s (1 + 2 3 q), u = 2us 3 q and ü = 2us 3 q leads to: 2mu s 3 q + Ku s 3/2 (1 + 2αu s 3 q)(1 + 2 3 q) 3/2 = N. (19) Now we can linearise the motion equation around the static equilibrium q = 0, that is:…”
Section: Appendix: Multi-asperity Contact Modelmentioning
confidence: 99%
“…When the slider and/or track are not perfectly rigid, and when the sliding speed is large enough, the interaction between the two rough surfaces is a succession of micro-impacts between antagonist asperities, which trigger a vibration of the solids, through not only their rigid body modes, but also their other eigenmodes. Overall, those vibrations are the source of the so-called roughness noise [16], the empirical laws of which have been studied extensively [17][18][19][20]. However, such empirical laws remain unexplained, and both numerical modelling [21] and statistical analyses [22] point towards the challenging need to better describe the forces involved in the individual, sub-millisecond-lived micro-impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Ben Abdelounis H [10] studied the friction noise between dry surfaces, and concluded that dry contact and roughness under light pressure were the main causes of the noise. Alain Le Bot E [11] explored the frictional noise of rough surfaces in contact with a light load. It was found that the main mechanism of sound generation was the normal vibration of the surface caused by the impact between opposing rough bodies, and the friction noise is dependent on the contact area of the rough surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that sound filters solid body vibrations because of own physical properties of wave media. Vibration of bearing components is also nonuniform physically based, but the lion’s share in noise components belongs to the friction noise (Bučinskas et al, 2010; Gharesi et al, 2018; Hruntovich et al, 2019; Le Bot and Bou Chakra, 2010; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%